EFFECT OF ADDITION SUGAR AND CARRAGENAN ON PHYSICS, CHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF SOFT CANDY CYTRUS CALAMANSI (Citrofortunella microcarpa) - Wuri Marsigit; Tuti Tutuarima; Ronny Hutapea (Jurnal Agroindustri, 2018)
The purpose of this study was to determine the effect of adding sugar and carrageenan on the physical, chemical an organoleptic characteristic of soft candy cytrus calamansi, and to get the best soft candy cytrus calamansi from the combination of treatment. This study used the RAK (Group Random Block Design) with two factors, the first factors were of adding 40g, 50g, and 60g sugar, and the second factors was the addition of 10g, 13g, and 16g carrageenan. Analysis of data used anova test and further test DMRT (Duncan Multiple Range Test). The results showed that the addition of sugar and carrageenan had significant effect on water content, and organoleptic soft candy of citrus calamansi, but ithere were not significant effect on ash, vitamin C, total acid content and pH.  The best treatment was found in the addition of sugar 60g and carrageenan 13g , with water content of 11.08%, ash content of 2.44%, pH 2.86, vitamin C 1.06 mg, total acid 0.65%.  The overall prference of  panelists liked the soft candy wtih the soft canddy by adding 65 g sugar and 13 g carragenan with  average score of 4.03 (level of likes ).